Pemberdayaan masyarakat berbasis wakaf uang - Al Arif, M; Rianto, Nur (UIN Sunan Kalijaga, 2010)
Waqf as one of the Islamic fiscal instruments has played a significant role in economic. Cash waqf is a new instrument in the field of waqf and Islamic economic as a facility for the purpose of worship and to achieve social welfare. The development of the waqf field through waqf funds, management which is flexible and offers many choices. The potential for cash waqf covers several aspects included for poverty alleviation program through community empowerment program. Cash waqf can give the contribution for the government community empowerment program.